PUBLIC VALUE PENGGUNAAN TRANSPORTASI UMUM FEEDER TRANS SEMARANG DI KOTA SEMARANG - Azkha Inhamuntasya; Satria Aji Imawan (Journal of Management and Public Policy, 2026)
Population growth and increased mobility in Semarang City have resulted in high private vehicle usage, leading to traffic congestion and congestion in various parts of the city. The Semarang City Government introduced the Trans Semarang Feeder as a feeder transportation mode integrated with the Trans Semarang BRT to improve public transportation accessibility and reduce dependence on private vehicles. However, in its implementation, there are still various public complaints regarding limited routes, waiting times, driver behavior, officer attitudes, and long travel times. This study aims to analyze the public value of using the Trans Semarang Feeder public transportation in Semarang City. The study used a descriptive qualitative method with the Public Value Scorecard approach from Peter Gomez and Timo Meynhardt which includes five dimensions, namely utilitarian-instrumental (usefulness), moral-ethical (feasibility), hedonistic-aesthetic (positive experience), political-social, and economic-financial. The results show that the Trans Semarang Feeder has provided benefits in terms of fare affordability. However, the public value formed is not fully optimal because there are still obstacles in route accessibility, waiting times, punctuality, security, and the quality of officer service. Therefore, improving service quality, staff professionalism, and operational system improvements are crucial steps to increase public value and encourage public interest in using public transportation.